The Relationship between Work Stress and Welfare in the Work Environment of employees during the COVID-19 Pandemic at PT. Saka Mitra Sejati Medan - Syafrizaldi Syafrizaldi; Nurul Nadia Zein (Budapest International Research and Critics University, 2020)
This study aims to determine the relationship between job stress and welfare in the work environment of employees during the Covid-19 pandemic at PT. Saka Mitra Sejati Medan. The results showed that there was a significant negative relationship between, with a value of r = -0.561 and a significance value (0.000). According to the descriptive data analysis results that have been presented, it can be seen from the mean score of the two variables, so that the difference test score can be calculated. So it can be concluded that the employees of PT. Saka Mitra Sejati Medan has low work stress and has high welfare in a work environment during the Covid-19 pandemic. Male employees have a lower mean value of work stress than women and have a higher mean value of welfare in the work environment than women. Employees with a work period of 6-8 years have the lowest mean value of work stress than employees with years of service below, and have a higher mean value of welfare in the work environment than employees with other tenure. The effective contribution of work stress variables to the welfare in the work environment is 31.5%, while the remaining 68.5% is influenced by other variables outside of this study. This can be seen from the R-square value (r2) obtained from the value of the relationship between work stress and welfare in the work environment of –0.561.